Do institutional structures matter? A comparative analysis of urban carbon management policies in the UK and Germany. (February 2016) - Marsden, Greg; Groer, Stefan
Abstract: The paper addresses the important question of how institutional structures matter to the delivery of climate change policy for urban transport. It examines the strategic goals, policy tools in operation and initial progress towards carbon emission reduction in seven cities across the UK and Germany where different institutional structures exist. The UK has the presence of a strong national carbon target and strong hierarchical national–local government relationships whilst Germany has a more integrated system of local transport provision in a context where local and regional government is stronger. Our findings show that the carbon agenda has made very little difference to what is happening on the ground in the cities. Across all sites, progress is being made but largely through technological improvements which are being almost completely offset by population growth. Even in the more integrated city environments there has not be an additional stimulus to manage the demand for travel. Contrary to previous research therefore, we cannot conclude that institutional structures are paramount in delivering effective carbon reduction policies. The institutional structures in the UK and in Germany are not perfectly aligned to carbon management but, given the cross policy impacts of most transport interventions, this is perhaps inevitable. We can clearly conclude however that "better" structures are not sufficient to achieve the implementation of more effective carbon policies. Whilst institutional structures must matter, it is the broader governance environment and the resources and politics involved in transport policy that currently seem to dominate the importance of the carbon agenda and implementation paths that emerge. Highlights: Provides a cross-national comparison of urban carbon reduction Identifies little stimulus for ambitious carbon reduction policies in all sites Institutional structures not currently as important as the political environment Pro-growth narrative and policies dominate the policy landscape. Co-benefits argument can help carbon reduction but can hide policy inconsistency